Studies on Fatty Acid Composition of Seeds of Improved Varieties of Cicer arietinum - Singhai, Benu; Shrivastava, S.K. (Asian Journal of Chemistry, 2010)
Five hybrid varieties of Cicer arietinum, viz., JGG-1, JG-218, JG-322, SAKI-93130 and JG-11 have been studied for their fatty acid composition by gas chromatography. The Cicer arietinum variety JGG-1 has highest (39.48%) total saturated fatty acids content and variety JG-322 has a rich (79.01%) total unsaturated fatty acids contents with better storage quality.